Muscular specifity and intensity in swimming against a mechanical resistance - Surface EMG in MAD and free swimming - Clarys, J. P.; Toussaint, H. M.; Bollens, E.; Vaes, W.; Huijing, P. A.; de Groot, G.; Hollander, A. P.; de Witte, B.; Cabri, J. (Swimming Science V, 1988)
The measurement of active drag using a MAD system provides a new approach to hydrodynamic analysis of the front crawl movement. The M..AD system allows swimming force recordings in a natural environment-water-and assumes that the turbulent flow around the moving body is the same in both MAD and free swimming. Even if these flows are different, the Reynolds number (R) range of the human body (6.6 x 105 < R < 3.9 x 106 ; see Figure 1) gives no indication whatsoever that the turbulence, and therefore total drag, could be altered or eventually reduced (Oarys, 1985). However, an adaptation of the swimmer's arm movements to the MAD system does occur, for the push-off is made against a fixed point. Evidence for this statement was collected from 9 subjects swimming similarly (slow and fast), both on the MAD system and freely, with underwater light trace photography including an acceleration indicator (through a stable multivibrator). Movement patterns of the foot (lamp at malleolus externus), the shoulder (lamp at acromion), and the hand (lamp at digitus minim us) were recorded and compared per individual. The movement patterns of feet and shoulder showed little or no differences. However, the hand movement pattern in all subjects was very much influenced and changed by the MAD system. Discrepancies occur in a steeper input-gliding phase, a missing S-shaped movement, and a nonexistent pull-push trajectory (Figure 2).